THE PERCENTAGE AND STRUCTURE OF PERODONT TISSUE DISEASES IN PATIENTS OF LVIV REGIONAL STATIONARY CLINICAL HOSPITAL DEPENDING ON AGE - M. М. Shevchuk (Український стоматологічний альманах)
Epidemiological studies of recent years have shown a high prevalence of periodontal tissue diseases in the world and in particular in Ukraine. Significant influence on the prevalence of periodontal tissue diseases in the population is caused by many factors: this is the climatic conditions of the area and the general level of health of the population and the ecological situation in Ukraine and social conditions of life. One of the main common factors in the development of periodontal tissue diseases is the presence of concomitant pathology. Despite the current trends in dentistry to improve diagnostic and treatment methods, the introduction of advanced medical technologies, a significant reduction in periodontal disease among adult Ukrainian population is not observed.